2010
DOI: 10.1258/om.2010.090057
|View full text |Cite
|
Sign up to set email alerts
|

Development of occult hepatitis B viral infection in pregnancy: implications for antenatal screening in women from endemic areas

Abstract: Summary: Occult hepatitis B virus (HBV) infection, manifest clinically by the presence of HBV deoxyribonucleic acid (HBV DNA) in peripheral blood in individuals who test negative for the HBV surface antigen (HBsAg), may occur in various clinical contexts, including under the influence of pharmacological immunosuppression in patients from areas endemic for HBV and, hence, at risk of previous exposure. Pregnancy is a condition associated with immune suppression, but whether virus-specific immunity may be suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Interestingly, four of the people with occult HBV infections were pregnant women ( Table 5 ). Pregnancy leads to a state of immune suppression which may enable the development of an occult infection, although this is yet to be verified [ 32 ]. This hypothesis however opens up a research gap on the relationship between pregnancy state and occult infection in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, four of the people with occult HBV infections were pregnant women ( Table 5 ). Pregnancy leads to a state of immune suppression which may enable the development of an occult infection, although this is yet to be verified [ 32 ]. This hypothesis however opens up a research gap on the relationship between pregnancy state and occult infection in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, such work has not been conducted among Egyptian population before. Vertical HBV transmission may occur in the OBI setting, 14 so screening for maternal HBsAg may be insufficient and should be supplemented with neonatal immune prophylaxis. 15 Our data showed that the frequency of positive total HBc Ab in the studied cases was 4.2%, and the frequency was statistically significantly increased in unvaccinated group when compared to the vaccinated group.…”
Section: Discussionmentioning
confidence: 99%
“…While this Th2-dominant phenotype at the maternal-fetal interface allows fetal survival, the presence of anti-inflammatory cytokines such as interleukin (IL)-4 and IL-10 may predispose to an increased risk of infection, including reactivation of latent viruses, such as HBV Chang et al, 2010. 14 However, the presence of anti-HBc is not an ideal marker for the diagnosis of OBI, it is recommended to be used as a surrogate marker whenever an HBV-DNA test is not available to identify potential seropositive OBI individuals, such as in cases of blood, tissue, or organ donation, or in cases of patients undergoing immunosuppressive therapy Raimondo et al, 2008. 19 In addition, anti-HBc determination is useful, even when HBV-DNA is available, because of the possibility of intermittent viremia.…”
Section: Discussionmentioning
confidence: 99%
“…One research demonstrates that HBV can be transferred from mother to child even if the mother is negative for HBsAg and positive for anti-HBc. 13 To examine infants at danger for vertical transmission of HBV infection, serologic screening of pregnant women includes test for HBsAg. It is not enough being unable to perceive occult hepatitis B virus infection.…”
Section: Introductionmentioning
confidence: 99%